과학교과 역량의 다면적 이해와 쟁점의 탐색: 일반 핵심역량과의 관계를 고려하여 - 이경건; Gyeong-geon Lee; 박정우; Jeongwoo Park; 이선경; Sun-kyung Lee; 홍훈기; Hun-gi Hong; 심한수; Han Su Shim; 신명경; Myeong-kyeong Shin (Journal of Science Education, 2019)
본 연구는 역량기반 교육과정 담론의 동향으로부터 과학과 핵심역량의 다면적 이해를 위한 쟁점을 탐색하고, 일반적 핵심역량과 과학 교과역량 간의 관계를 고찰하고자 하였다. 먼저는 행동주의, 인문주의, 그 포괄적 종합을 중심으로 역량기반 교육과정의 이론적 배경을 살펴보았다. 이후 OECD의 역량 관련 프로젝트(DeSeCo; OECD Education 2030), 미국의 차세대 과학 표준(NGSS), 한국의 2015 개정 교육과정을 역량기반 교육과정의 관점에서 검토하였다. 이와 함께 국내외에서 핵심역량 및 교과역량에 관하여 작성된 주요 문헌 15건이 제시하는 105개의 일반역량 및 45개의 과학역량을 정리하고 체계적으로 분석하였다. 연구 결과 첫째, 역량의 정의 및 범주화를 위한 쟁점에 관하여, 일관된 체계 내에서 제시되는 역량들이 일종의 포괄성을 지닌다고 할 때, 역량의 적절한 개수의 문제, 역량의 적절한 층위 문제, 개별 역량들이 얼마나 고유하고 독립적이어야 하는가의 문제를 지적하였다. 둘째, 문헌별 역량 요소들의 경향성으로서 역량 항목들이 개인적-미시적 차원, 공동체적-중시적 차원, 사회적-거시적 차원에서 다양하게 제시됨을 확인하였으며, 일반역량과 교과역량 모두에서 중시적 차원이 강조되고 있음을 밝혔다. 셋째, 일반역량과 교과역량간 관계에 있어서 일반역량은 거시적 차원을 강조하고 교과역량은 미시적 차원을 강조하는 경향에서 간극이 발생함을 밝힘으로써, 양자가 서로 맞닿을 수 있는 부분은 중시적 차원이라는 점에 주목하였다. 이러한 논의는 2015 개정 교육과정을 비롯한 국가교육과정에서의 역량 이해 및 추후 개발을 위하여 적지 않은 통찰을 제공할 것으로 생각된다. The purpose of this study is to explore the multi-faceted understanding and issues of science subject matter competencies from the trends of competency-based curriculum discourse, and to examine the relationship between general core competencies and science subject matter competencies. First, we examined the theoretical background of competency-based curriculum focusing on behaviorism, humanism, and its comprehensive synthesis. After that, we reviewed OECD's competency-related projects (DeSeCo; OECD Education 2030), US Next-Generation Science Standards (NGSS) and Korea's 2015 Revised National Curriculum from the viewpoint of competency-based curriculum. After that, we summarized and systematically analyzed a list of competencies, 105 general core competencies and 45 science subject matter competencies proposed by 15 important documents from home and abroad. The results of this study are as follows: First, the issues of the proper number, appropriate dimension, and how individual competencies should be unique and independent were pointed, in terms of defining and categorizing competencies. Second, it was suggested that the competency items are presented in various dimensions such as personal-micro dimension, community meso-dimension, and social-macro dimension. Meso-dimension was placed on both general core competencies and subject matter competencies. Third, in the relationship between general core competencies and subject matter competencies, the former emphasizes macro-dimension, and the latter emphasizes micro-dimension, revealing an existing gap, and where the two can meet each other is the meso-dimension. These discussions are thought to provide insight into the understanding of competencies in the national curriculum, including the 2015 Revised National Curriculum.